Diagnosis and treatment of brain injury complicated by hypernatremia - Wu, Hao; Bai, Ming; Li, Xiayin; Xing, Yan; Sun, Shiren (Frontiers in Neurology, 2022)
Hypernatremia is a common electrolyte disorder in patients with brain injury. The mortality of patients with brain injury complicated by severe hypernatremia could be as high as 86.8%. The efficacy of conventional treatment for hypernatremia is limited. Continuous renal replacement therapy (CRRT) could slowly, controllably, and continuously reduce the blood sodium concentration and gradually become an important treatment for severe hypernatremia patients. This review aims to provide important information for clinicians and clinical researchers by describing the etiology, diagnosis, hazards, and conventional treatment and CRRT treatment of hypernatremia in patients with brain injury.